Pollination under attack: First insights from Türkiye Plain reveal microplastics in bees from both urban and rural areas - Abdullah Altunışık; Damià Barcelò; Luca Gallitelli (Ecological Indicators)
The increasing production and environmental release of plastics have led to the widespread presence of microplastics (MPs) in diverse ecosystems. Pollinators, such as honeybees (Apis mellifera), are particularly vulnerable to MP exposure due to their foraging behavior, which brings them into contact with contaminated environmental matrices, including air, water, and floral resources. This study aims to investigate the presence, characterization, and potential ecological implications of MPs in honeybees from two distinct regions in Türkiye: a polluted urban area and a pristine rural area. Honeybee samples were collected, digested, and analyzed for MP presence using ATR-FTIR spectroscopy. Our findings confirm the presence of MPs in honeybees from both study sites, with a significantly higher concentration in the urban area (p < 0.01). The majority of detected MPs were fibers (76 %), followed by fragments (19 %) and films (5 %). Five polymer types were identified, with polyethylene terephthalate (PET) being the most prevalent. Concerning the health index, 90.5 % of bees were found dead, while 9.5 % were alive. MPs in honeybees suggest potential implications for pollination services and pollinator health. This study highlights the need for further research on the ecological consequences of MP contamination in pollinators and its potential cascading effects on biodiversity and agricultural productivity.